Implementation of Dialogue Journal in Teaching Writing Descriptive Text - Jauhar Helmie (IJET (Indonesian Journal of English Teaching), 2019)
Dialogue Journals Writing (DJW) or Written Dialogue Journals are written dialogues or conversations between students and teacher kept in a personal journal book over period of time on a particular topic preferred by both the students and the teacher (Peyton and Reed, 1990; cited from Collin (2003). This study explored the implementation of dialogue journal as media in teaching writing descriptive text. The subjects of this study were students at Eleventh Grade of vocational high school. This study is qualitative case study which conducted in three meetings. The data were obtained from classroom observations, documentations from the learners and questionnaire. The result of document analysis showed that the students’ writing was poor. It can be seen from the students’ writing performance which was analyzed based on the writing indicator by Brown and Abeywiakram (2010). However, from the students’ dialogue showed that the students could understand the content of their friends’ writing. Also from the students’ dialogue, they could express their feelings toward their friends’ writing. While the result of classroom observation showed that the implementing of DJW brought new atmosphere for the students during learning activity. They could enjoy the learning while writing descriptive text through DJW. Meanwhile the result of questionnaire showed that students gave positive response toward implementing DJW. As the suggestions, the use of Dialogue Journal can be solution for the students who lack of practice writing. Moreover, it can build their writing habit. Thus, the teacher can use Dialogue Journal in learning activity.